An analysis of the science programs of selected DOD Schools at Clark Air Base - Goff, Edward Peter (1977)
This research attempted to determine how science programs at selected elementary DOD schools of Clark Air Base, Philippines relate to the following: 1.) the preparation of the teachers, 2.) the science objectives, 3.) the structure and science content, 4.) methods and procedures, and 5.) evaluation of the programs of science teaching currently existing in the above schools used for the research. The descriptive survey method was used. The faculties of Grissom, MacArthur, Lily Hill and Wurtsmith Schools returned 65 survey forms. Teachers were asked to respond to items which dealt with the general education background and specific science training, the relationship of science objectives to existing science programs, methods and procedures being practiced, and types of evaluation of science programs being utilized.
Appendices: leaves 105-127.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Science -- Study and teaching (Elementary) -- Philippines -- Clark Air Base, Pampanga